Liberia [In West African agriculture and climate change: A comprehensive analysis] - Karmouth, Benjamin S. Jr.; Jalloh, Abdulai; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2013)
Liberia is situated at the southwest corner of the West Coast of Africa. It lies between the longitudes of 7°30´ and 11°30´ west and latitudes 4°18´ and 8°30´ north. It covers a surface area of about 111,370 square kilometers (about 43,506 square miles). The extent of its dry land is 96,160 square kilometers or 37,570 square miles (UNDP Liberia 2006). Liberia is bordered on the west by Sierra Leone, on the north by Guinea, on the east by Côte d’Ivoire, and on the south by the Atlantic Ocean. The country has two seasons: rainy and dry. The rainy season lasts from May to October, and the dry season runs from November to April. The farming system is characterized by shifting cultivation, which has led to the conversion of extensive areas of forest into farmland and grassland in many parts of the country. Rice is the staple food of Liberians, while cassava is the second major foodcrop. Overall, Liberian farmers are resource poor and invariably produce at a subsistence level. Against the background of limited resources, the typical Liberian farmer is faced with numerous biophysical constraints, including low-yielding crop varieties, pests, and diseases, as well as poor soil conditions. Heavy reliance on rainfall exposes farmers to the vagaries of the weather. There are 700 kilometers of paved roads in Liberia, extending from Monrovia to Bo Waterside (on the Sierra Leone border), Ganta, and Buchanan Counties, making these areas easily accessible; they are very different from the 1,600 kilometers of unpaved roads, mostly in need of repair, that make it difficult to transport agricultural products from the southeastern counties to Monrovia.